Pelatihan Sistem Informasi Bagi UMKM Produksi Mie Dan Baso Di Kecamatan Bojongloa Kidul Bandung - Marvin Chandra Wijaya (Universitas Lancang Kuning, 2022)
Currently, small business actors or economies are the backbones of the Indonesian economy. Information systems for managing business administration are very important and require computers and digital information knowledge. Currently, the noodle and meatball production business use a manual recording system. The training is given to small businesses that produce noodles and meatballs in Bojongloa Kidul District in Bandung City using the Microsoft Excel program. The training provided is specific to the needs of small businesses producing noodles and meatballs. After the training was given, the noodle and meatball production business implemented a computerized administrative system. The successful computerized administration systems are raw material stock management, finished goods stock management, product purchasing, and sales management. The training results are expected to bring progress and efficiency in the management of small businesses that produce noodles and meatballs.